Movilidad y redes de influencia de los seviros Augustales en Baetica - Barrón Ruiz de la Cuesta, Alberto (Collectanea Philologica, 2022)
The seviratus Augustalis was an urban institution of semi-official nature which was mainly held by wealthy freedmen. It appeared in Italy in the end of the 1st century BC and spread fast to the Latin-speaking provinces of the Roman Empire. It had an essential role in the growth of the economic and commercial activities of several cities till the 3rd century AD. This position has been studied by many scholars through its abundant epigraphic evidences. The scarcity of mentions to the seviri Augustales in the Roman literature has impeded the elucidation of its concrete functions. It has clear similarities with some priesthoods and urban magistratures, but the seviri Augustales lacked the status and the official nature of them. This unofficial essence was the point which made possible the development of the seviratus Augustalis as a tool for the social promotion of rich freedmen, whose admission to magistratures and priesthoods was forbidden. The goal of the current analysis is to identify the economic and institutional connections between the seviri Augustales of Baetica, both inside and outside this Hispanic province. The preserved epigraphic evidence illustrates the diffusion of this institution in the south of Roman Hispania and the importance of the economic route through the course of the Guadalquivir River, as well as the commercial contacts between diverse coastal cities of Hispania and other Roman regions. Funding: Este artículo se ha realizado en el marco del proyecto de investigación HAR2017-84711-P del Ministerio de Economía y Competitividad del Gobierno de España. Asimismo, resultó de gran utilidad para su elaboración la estancia de investigación realizada en la Fondation Hardt pour l’étude de l’antiquité classique, ubicada en la ciudad de Ginebra (Suiza).